2021
DOI: 10.3389/fbioe.2020.574006
|View full text |Cite
|
Sign up to set email alerts
|

Control Modification of Grasp Force Covaries Agency and Performance on Rigid and Compliant Surfaces

Abstract: This study investigated how modifications in the display of a computer trace under user control of grasp forces can co-modulate agency (perception of control) and performance of grasp on rigid and compliant surfaces. We observed positive correlation (p < 0.01) between implicit agency, measured from time-interval estimation for intentional binding, and grasp performance, measured by force-tracking error, across varying control modes for each surface type. The implications of this work are design directiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 90 publications
(109 reference statements)
1
8
0
Order By: Relevance
“…In this way, action initiation is tightly coupled with the sensory consequence. In this study, we follow a template from our previous works (Nataraj et al, 2020a; Nataraj et al, 2020b; Nataraj & Sanford, 2021 ) whereby we examine an ‘extended’ action with a prolonged movement phase (e.g., reach) prior to a terminating action (e.g., grasp). This approach was necessary to allow participants to ‘experience’ the effects of each control mode and modulate perception before the grasp action, which ultimately incited the sound beep.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, action initiation is tightly coupled with the sensory consequence. In this study, we follow a template from our previous works (Nataraj et al, 2020a; Nataraj et al, 2020b; Nataraj & Sanford, 2021 ) whereby we examine an ‘extended’ action with a prolonged movement phase (e.g., reach) prior to a terminating action (e.g., grasp). This approach was necessary to allow participants to ‘experience’ the effects of each control mode and modulate perception before the grasp action, which ultimately incited the sound beep.…”
Section: Discussionmentioning
confidence: 99%
“…The perceived time-intervals were shorter after voluntary actions, which is assumed to be associated with more control and a perceived sense of agency. While recent studies have suggested a disconnect between binding and intentional action ( Kirsch et al, 2019 ; Suzuki et al, 2019 ), multisensory causal binding reflected through varied perceptions in time has an apparent positive link to hand functions performed through computerized interfaces (Nataraj et al, 2020a; Nataraj et al, 2020b; Nataraj & Sanford, 2021 ). As such, time-perception metrics may still be a window into sensory-based motor learning ( Adamovich et al, 2009 ; Sanford et al, 2020 ) as done with VR rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“…Self-report is a subjective way to evaluate the sense of agency, which is the only method adopted in most works. Beyond self-report, intentional binding as one implicit method of the agency has been used in several interaction tasks recently (Suzuki et al , 2019; Nataraj et al , 2020 a ; Van den Bussche et al , 2020; Nataraj and Sanford, 2021). The standard basis of the intentional binding paradigm is the estimation of the time interval between an action (e.g., a button press) and a sensory result (e.g., sound feedback) (Suzuki et al , 2019; Nataraj et al , 2020 a , 2020 b ; Van den Bussche et al , 2020; Nataraj and Sanford, 2021).…”
Section: Related Workmentioning
confidence: 99%
“…Beyond self-report, intentional binding as one implicit method of the agency has been used in several interaction tasks recently (Suzuki et al , 2019; Nataraj et al , 2020 a ; Van den Bussche et al , 2020; Nataraj and Sanford, 2021). The standard basis of the intentional binding paradigm is the estimation of the time interval between an action (e.g., a button press) and a sensory result (e.g., sound feedback) (Suzuki et al , 2019; Nataraj et al , 2020 a , 2020 b ; Van den Bussche et al , 2020; Nataraj and Sanford, 2021). It is an implicit way to evaluate the agency by measuring the time perception of the action effect, and participants are asked to estimate the time interval between action and consequence.…”
Section: Related Workmentioning
confidence: 99%
“…Due to the development of artificial intelligence for signal processing (Wan et al , 2021; Yu et al , 2022), EEG becomes a valuable and popular tool for evaluating the user's experience when interacting with the product or system. Based on EEG analysis, the alpha band has been proven to be highly related with SoA, not only alpha power (Zito et al , 2020; Nataraj and Sanford, 2021), but also alpha coherence (Mathewson et al , 2011). However, little was known in the existing literature on SoA evaluation using EEG data during continuous manipulation (Wen et al , 2017), such as CAD operations.…”
Section: Introductionmentioning
confidence: 99%